Clinical Guide to Popular Diets - Apovian, Caroline (CRC Press)
Contenido: 1) La dieta Atkins; 2) Dieta DASH; 3) iDiet; 4) La dieta mediterránea; 5) La dieta Paleo; 6) La dita Playa del Sur; 7) Dietas veganas; 8) La dieta Weight Watchers; 9) La dieta de la Zona.